Information and Communication Technology for Intelligent Systems Proceedings of ICTIS 2018, Volume 1 - Satapathy, Suresh Chandra; Joshi, Amit.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book gathers papers addressing state-of-the-art research in all areas of Information and Communication Technologies and their applications in intelligent computing, cloud storage, data mining and software analysis. It presents the outcomes of the third International Conference on Information and Communication Technology for Intelligent Systems, which was held on April 6-7, 2018, in Ahmedabad, India. Divided into two volumes, the book discusses the fundamentals of various data analytics and algorithms, making it a valuable resource for researchers' future studies. .
Semantic Segmentation using Deep learning for Brain Tumor MRI via Fully Convolution Neural Networks -- An Efficient Cryptographic Mechanism to Defend Collaborative Attack against DSR Protocol in Mobile Adhoc Networks -- Materialized Queries with Incremental Updates -- Traffic Signal Automation through IoT by Sensing and Detecting Traffic Intensity through IR sensors -- Performance Evaluation of Various Data Mining Algorithms on Road Traffic Accident Dataset -- Classification of Blood Cancer and form associated Gene networks using Gene Expression Profiles -- Stock Market Decision Making Model based on spline approximation using minimax criterion.
Keywords: Computational intelligence; Big data; Signal processing; Computational Intelligence; Big Data; Signal, Speech and Image Processing